DAMPAK KEHADIRAN BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT(BHABINKAMTIBMAS) DALAM PENANGANAN TINDAK PIDANA RINGAN (TIPIRING) DIWILAYAH HUKUM POLSEK MATUR KABUPATEN AGAM - amri, khairul (Jurnal Ilmiah Hukum dan Keadilan, 2023)
Security disturbances are events that cause disruption of security stability in the community, both criminal and social problems, which are now familiar to some Indonesian people, so it is deemed necessary to adopt the concept of Community Policing (Community Policing) or commonly abbreviated as "Polmas". In order to create security in the community, the National Police are given the task according to the law so that the Police are able to create comfort and security in the community. The spearhead of the implementation of community policing is the Bhayangkara Supervisor of Community Security and Order (BHABINKAMTIBMAS) who is a Community Officer (Police Officer) who is a member of the National Police in charge of fostering Bhabinkamtibmas and is also a Polmas officer in the Village/Kelurahan. The main problem examined in this study is 1. How Bhabinkamtibmas in fostering security in the Matur community; 2. What is the impact of the presence of Bhayangkara, the builder of public security and order (Bhabinkamtibmas) of the National Police in handling minor crimes (Tipiring) in the jurisdiction of the Matur Police, Agam Regency. The research method used in this research is empirical juridical also known as field research. Data sources consist of primary data and secondary data. Data was collected by means of interviews and document studies. Then the data collected was analyzed qualitatively. The results of the study indicate that Bhabinkamtibmas has the main task of fostering security and order in the Matur community and the impact of the presence of Bhabinkamtibmas Polri in handling minor crimes at the Matur Police